Injury Characteristics and Microbial Resistance Patterns in Infections of Open Tibia Fractures (Eastern Medical College Journal, 2026)
Background: Tibial fractures are the most frequent open fractures and frequently accompanied by other injuries, which were high vigor injuries.Materials and Methods: A hospital-based cross-sectional study was done among 608 patients to assess the injury characteristics and resistance patterns of microorganisms involved in the infection of open fracture tibia at the National Institute of Traumatology and Orthopedic Rehabilitation (NITOR), Dhaka. Results: The mean age of the patient’s was 36.2±15.5 years. Gustilo III was higher injury (72.1%) and Gustilo subtype IIIB was the predominant (37.5%). Gustilo type II infection was higher injury (31.3%). Positive surveillance culture was found among the 38.2% patients at admission. The contamination rate decreased to 26.2% after debridement and 12.0% of patients became contamination free. The infection rate from the ward samples again elevated to 44.4% from post debridement contamination of 26.2% which indicates hospital acquired infection. Gram-negative organisms were common with multidrug resistance. Pseudomonas and Klebsiella species are only sensitive to Imipenem and Meropenem only around 49-70%. Cotrimoxazole and Chloramphenicol also showed good sensitivity against both Staphylococcus aureus (90.9%) and E. coli (69-75%).Conclusion: Regrettably, hospital-acquired infections are frequent in orthopaedics admitted patients where Gram-negative organisms were predominant and the antibiograms indicated concerning patterns of treatment resistance. Surgical debridement is useful in decreasing contamination from the open fracture wound.Eastern Med Coll J. July 2025; 10 (2): 116-121